Efficacy and safety of lixisenatide in Japanese patients with type 2 diabetes mellitus inadequately controlled by sulfonylurea with or without metformin: Subanalysis of GetGoal‐S. Issue 2 (24th September 2014) - Onishi, Yukiko; Niemoeller, Elisabeth; Ikeda, Yukio; Takagi, Hiroki; Yabe, Daisuke; Seino, Yutaka
Abstract Aims/Introduction This was a subanalysis of Japanese patients included in the glucagon‐like peptide‐1 receptor agonist AVE0010 in patients with type 2 diabetes mellitus for glycemic control and safety evaluation (GetGoal‐S) study – a 24‐week, randomized, placebo‐controlled study of lixisenatide in patients with type 2 diabetes mellitus inadequately controlled by sulfonylurea with or without metformin. Materials and Methods In GetGoal‐S, 127 Japanese patients received the once‐daily prandial glucagon‐like peptide‐1 receptor agonist lixisenatide 20 μg/day or a matching placebo. The primary outcome was change in glycated hemoglobin. Results At week 24, lixisenatide significantly reduced mean glycated hemoglobin (least squares mean difference vs the placebo −1.1% [12 mmol/mol, P < 0.0001]), and significantly more lixisenatide patients reached glycated hemoglobin targets of <7% (53 mmol/mol) and ≤6.5% (48 mmol/mol) vs the placebo. Lixisenatide produced statistically significant reductions in 2‐h postprandial plasma glucose (least squares mean difference vs the placebo −8.51 mmol/L, P < 0.0001) and glucose excursion vs the placebo, and significantly reduced fasting plasma glucose (least squares mean difference vs the placebo −0.65 mmol/L, P = 0.0454). Bodyweight decreased with both lixisenatide and the placebo (least squares mean change −1.12 kg for lixisenatide, −1.02 kg for placebo). The overall incidence of adverse events was similar for lixisenatide and the placebo (84.2 and 82.4%, respectively), the most frequent being gastrointestinal disorders (52.6% for lixisenatide vs 29.4% for placebo). The incidence of symptomatic hypoglycemia was higher with lixisenatide vs the placebo (17.1 and 9.8%, respectively), with no cases of severe symptomatic hypoglycemia in either group. Conclusions In the Japanese subpopulation of the GetGoal‐S study, lixisenatide produced a significant and clinically relevant improvement in glycated hemoglobin, with a pronounced improvement in postprandial plasma glucose, and a good safety and tolerability profile.